Automated Paraphrasing of Portuguese Informal into Formal Language (Linguamática, 2019)
This paper presents the automation process of paraphrasing and converting Portuguese constructions typical of informal or spoken language into a formal written language. We illustrate this automation process with examples extracted from the e-PACT corpus that involve the placement of clitic pronouns in verbal compound contexts. Our task consists in paraphrasing and normalizing, among others, constructions such as vou-lhe/posso-lhe fazer uma surpresa into vou/posso fazer -lhe uma surpresa (I will/can_to him/her make a surprise / I will/can make_to him/her a surprise; I will/can make him/her a surprise), where the clitic pronoun lhe migrates from an enclitic position immediately after the first verb of the verbal compound to an enclitic position after the main verb, which is the verb responsible for the selection of that pronominal argument. The first verb is either an auxiliary verb or a volitive verb, e.g., quere "want". This is a standard revision procedure in European Portuguese. Cases like this represent linguistic phenomena where language students and language users in general get confused or "stumble". The paper focuses on general language where the phenomena being observed occur, describes examples of interest found in the corpus, and presents an automatic solution for the normalization of informal syntactic inadequacies found in the researched structures into standard structures typical of formal or professional writing through the application of very generic transformational grammars.